FDI liberalization, firm heterogeneity and foreign ownership: German firm decisions in reforming India - Holger Görg; Henning Mühlen; Peter Nunnenkamp (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
The paper investigates the role of firm-level productivity and industry-level R&D for MNEs' choice of undertaking FDI, and the share of ownership in foreign affiliates. Two firm-specific datasets on German MNEs with varying equity stakes in Indian affiliates are used to account for the two-step decision process. The paper also analyses how German firm decisions were affected by the liberalisation of FDI regulations in India. Results show remarkable differences between the selection and the ownership share equation, and also between the pre-reform and post-reform periods. The evidence clearly reveals the tradeoffs involved in selective FDI approvals and foreign ownership restrictions.
Keywords: F23; L25; 330; multinational enterprises; firm characteristics; selective FDI approval; German FDI; ownership share; Heckman model